Dexamethasone conjugation to an Avidin-Nucleic-Acid-NanoASsembly eliminates the steroid plasma absorption, enhancing selective lung tropism in a murine model of pulmonary fibrosis - Annalisa Morelli; Elisa Schiavon; Martina Bruna Violatto; Giulia Yuri Moscatiello; Anita Salmaso; Alice Passoni; Alessia Lanno; Simone Bernardotto; Martina Stocco; Andrea Mattarei; Renzo Bagnati; Federica Meloni; et al. (Drug Delivery)
Despite their anti-inflammatory activity, corticosteroids are limited in clinic due to poor selectivity and their side effects. The ability to cross biological barriers makes them powerful yet unspecific, leading to toxicity and a low therapeutic index that limits their chronic use in autoimmune, inflammatory, and infectious diseases. It is needed another approachfor innovative targeted delivery strategies. This study aimed at investigating if the dexamethasone conjugation to Avidin-Nucleic-Acid-NanoASsembly (ANANAS) could allow its selective lung release in the bleomycin-induced pulmonary fibrosis model. Since recent evidence showed a selective ANANAS accumulation in macrophage lysosomes in a liver fibrosis model, an acid-sensitive hydrazone linker was used to facilitate dexamethasone release into pulmonary macrophages, key players in lung fibrosis. Systemic ANANAS-Dex administration in healthy mice showed no dexamethasone release in plasma or peripheral organs, with delivery exclusively targeting the liver, independent of the health status. While this confirmed the nanocarrier safety, it underscored the influence of the administration route, rather than the disease state, on ANANAS-Dex tropism. The study on intranasal administration highlighted that: 1) free Dex circulates in the bloodstream, while ANANAS keeps the drug confined in the lungs; 2) ANANAS-Dex results in sustained drug release in the lungs, enhancing the lungs/plasma-peripheral organs ratio; 3) fibrotic mice exhibited prolonged kinetics and macrophage targeting. Based on the biodistribution and pharmacokinetics studies, it is possible to achieve controlled and safe steroid release in lung disorders, reducing systemic toxicity and potentially enhancing clinical compliance.